Law and economics in Jane Austen - Kohm, Lynne Marie (Lexington Books, 2020)
"Law and Economics in Jane Austen traces legal and economic principles in sex, marriage, and romance as set out in Austen's novels, unveiling how those meticulous principles control today's modern romance. Culture may have changed in the past 300 years, but these rules remain and even now shape modern romance"--